INOVASI PAKAN ALTERNATIF UNTUK PRODUKTIVITAS BUDIDAYA LELE - Euis Rosidah; Rani Rahman; Irman Firmansyah; Kurniawan Kurniawan (Jurnal Pasca Dharma Pengabdian Masyarakat, 2022)
This service activity is intended for communities affected by COVID-19 located in Margahayu Village, Manonjaya District, Tasikmalaya Regency, which had previously been fostered in the management of catfish cultivation. The problem raised is the lack of human resources that can be creative and innovate properly regarding the manufacture of alternative feed for catfish to increase efficiency and economic value. Currently, the high price of feed is a problem for the sustainability of catfish cultivation. Magot cultivation training is a solution to solve these problems. The training was carried out for one day, from explaining the benefits of magot to cultivation techniques: making fly nests, mating flies, hatching eggs into pufa, enlargement into magots, and growing into flies. However, the assistance is carried out for one month. Participants were given education about this cycle process by utilizing organic food waste into feed for magot so that costs become efficient to reduce the cost of feed that has been happening so far. The activity results show that feed cultivation has been successfully carried out even though the magot production exceeds the capacity of the space provided.